KESALAHAN PENERAPAN EJAAN BAHASA INDONESIA PADA TUGAS AKHIR MAHASISWA - Sri Murniati (STKIP Siliwangi, 2022)
Errors in the application of Ejaan Bahasa Indonesia (EBI) in students' final assignments (TA) have the opportunity for ambiguity to occur so that the contents of the writing are less communicative. The purpose of this study was to describe errors in the application of EBI and the relationship between error variables in TA students of D-4 Study Program of Building Maintenance and Repair Engineering and Road and Bridge Design Engineering Study Program, Civil Engineering Department, Bandung State Polytechnic. This research is qualitative and quantitative with thirty TA data as samples taken at random in the department's library. The results showed that there were 544 spelling errors consisting of: 180 capital letter writing errors, 43 word writing errors, 38 numeric errors, and 7 cursive letter errors. There were 276 punctuation errors, consisting of: 142 comma errors, 82 period errors, 40 colons, and 12 semicolon errors. The results of the quantitative analysis show that the number of errors between the variables is relatively the same. The highest number of spelling errors was caused by errors in the use of capital letters, which was 64.4%. Most other errors are caused by sign point and word writing errors.